2002
DOI: 10.1111/1469-8986.3960869
|View full text |Cite
|
Sign up to set email alerts
|

Memory‐based detection of task‐irrelevant visual changes

Abstract: Colored grating patterns were presented to 8 participants in a passive oddball condition (standard, 87.5% and deviant, 12.5%, differing in their color). In the corresponding multicolor condition, grating patterns of eight different colors were presented, their probabilities set equal both to each other and to that of the deviant in the oddball task. Compared with the ERP response elicited by the standard stimulus, the deviant response was negatively displaced over posterior areas, the difference wave peaking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
216
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(250 citation statements)
references
References 4 publications
29
216
5
Order By: Relevance
“…However, the memory-based interpretation of change-related positivity must be treated with caution at least for two reasons. First, several studies reported that memory-based change detection in the visual modality was reflected by a posterior negativity (i.e., visual MMN) (e.g., Czigler et al, 2002;Heslenfeld, 2003;Winkler et al, 2005). Although the change-related positivity and the visual MMN have a similar latency and scalp-distribution, further study is necessary to systematize the relationship of the two components with inversed polarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the memory-based interpretation of change-related positivity must be treated with caution at least for two reasons. First, several studies reported that memory-based change detection in the visual modality was reflected by a posterior negativity (i.e., visual MMN) (e.g., Czigler et al, 2002;Heslenfeld, 2003;Winkler et al, 2005). Although the change-related positivity and the visual MMN have a similar latency and scalp-distribution, further study is necessary to systematize the relationship of the two components with inversed polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Visual MMN at around 100-300 ms can be elicited by the infrequent deviant stimuli presented at unattended locations, which suggests the existence of pre-attentive change detection in the visual modality (e.g., Alho et al, 1992;Czigler et al, 2002Czigler et al, , 2004Heslenfeld, 2003;Kenemans et al, 2003;Lorenzo-Lopez et al, 2004;Mazza et al, 2005;Pazo-Alvarez et al, 2004;Stagg et al, 2004;Winkler et al, 2005). For the functional significance of visual MMN, however, two contrasting hypotheses have been proposed: memory-based comparison hypothesis and different refractoriness state hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that alcohol considerably decreased the vMMN amplitude for changes in peripheral stimulus location and duration whereas that for color change was not affected. The latter might be due to the physical stimulus properties e no reliable vMMN emerged to the green color deviant (compared to the sea-green standard), implying a relatively high level of change is required to elicit the color vMMN at first place (Czigler et al, 2002). An additional aspect (beside basic experimental design) that discriminated the two vMMN and alcohol studies was the usual amount of alcohol the participants consumed being considerably higher in Kenemans et al's study (15e20 standard drinks/week) than in He et al's study (3e12 standard portions/months) that may have led to shorter memory traces to begin with in the more drinking sample (e.g., Ahveninen et al, 1999).…”
Section: Substance Abusementioning
confidence: 99%
“…There has been some suggestion that the left cerebral hemispheric areas implicated in important language functions may serve as a top-down control source that modulates the activity level of the visual cortex (24)(25)(26)(27)(28), but little is known about whether this lateralized effect occurs at early, preattentive perceptual processing stages or at postperceptual decision/response phases. Visual mismatch negativity (vMMN) is widely held to reflect the brain's early and automatic change in event-related potentials (ERPs) in response to a novel stimulus (29)(30)(31). In the present study, the vMMN component is observed in order to assess the lateralized Whorfian response to task-irrelevant changes in color stimuli.…”
mentioning
confidence: 94%